2018
DOI: 10.1104/pp.18.01042
|View full text |Cite
|
Sign up to set email alerts
|

ARSENATE INDUCED CHLOROSIS 1/ TRANSLOCON AT THE OUTER ENVOLOPE MEMBRANE OF CHLOROPLASTS 132 Protects Chloroplasts from Arsenic Toxicity

Abstract: widely distributed in the environment. In some areas of south and southeast Asia, agricultural soils are contaminated with As due to mining, irrigation with As-laden groundwater, and industrial activities, resulting in increased risk of As accumulation in crop plants (Meharg and Rahman, 2003;Williams et al., 2009). High As concentrations in crop plants can present a significant risk to human health through dietary exposure Zhao et al., 2010). In more heavily contaminated soils, crop plants may suffer from phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…The Chl a and Chl b content significantly declined by 2.6‐fold and 1.6‐fold in Khitish, respectively, and 2.2‐fold and 1.8‐fold in Muktashri, respectively (Table 2). Several studies have shown As‐induced injury to the chlorophyll apparatus due to decline in pigment biosynthesis or activation of enzymes leading to disintegration of the porphyrin ring (Wang et al, 2018). Exogenous Mel lowered the As‐induced loss of Chl a and Chl b content by 1.8‐fold and 1.3‐fold in Khitish, respectively, and 1.8‐fold and 2.4‐fold in Muktashri, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chl a and Chl b content significantly declined by 2.6‐fold and 1.6‐fold in Khitish, respectively, and 2.2‐fold and 1.8‐fold in Muktashri, respectively (Table 2). Several studies have shown As‐induced injury to the chlorophyll apparatus due to decline in pigment biosynthesis or activation of enzymes leading to disintegration of the porphyrin ring (Wang et al, 2018). Exogenous Mel lowered the As‐induced loss of Chl a and Chl b content by 1.8‐fold and 1.3‐fold in Khitish, respectively, and 1.8‐fold and 2.4‐fold in Muktashri, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The Chl a and Chl b content significantly declined by 2.6-fold and 1.6-fold in Khitish, respectively, and 2.2-fold and 1.8-fold in Muktashri, respectively (Table 2). Several studies have shown As-induced injury to the chlorophyll apparatus due to decline in pigment biosynthesis or activation of enzymes leading to disintegration of the porphyrin ring (Wang et al, 2018 2). The reducing power of any species is characteristic of the innate capacity to donate a hydrogen atom to free anionic superoxide radical so as to terminate free-radical reactions (Basu et al, 2010).…”
Section: Effect Of Mel On Oxidative Damage-related Parametersmentioning
confidence: 99%
“…4 ) was quite higher for plants growing on VM comparatively to CAR soil. Arsenic is extremely toxic for chloroplasts where it links to dithiol compounds and enzyme containing closely spaced Cys residues [ 57 ]. Other elements such as Zn may also be toxic in chloroplasts [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Structural alterations including the absence of palisade structure, reduced leaf thickness, and structural damage in chloroplasts and mitochondria have been observed in plants intoxicated by trace metals (Bini et al, 2012;Wang et al, 2018b), leading to decreased photosynthesis and respiration (Ghori et al, 2019). Chloroplasts appear to be a sensitive target of As toxicity and AtTOC132 (Translocon at the Outer Envelope Membrane of Chloroplast 132) plays a role in protecting chloroplasts from As toxicity in A. thaliana (Wang et al, 2018b). Trace metals at toxic levels also interfere with the uptake and transport of nutrients and water (Perfus-Barbeoch et al, 2002;Lešková et al, 2021).…”
Section: Physiological Disturbancementioning
confidence: 99%